Colour properties of poly(vinyl alcohol)–anthocyanin blends - Aziz, N.; Mat Nor, N.A.; Mohd-Adnan, A.F.; Taha, Rosna Mat; Arof, Abdul Kariem (Springer, 2016)
This work aims to analyze the colour variation and stability of anthocyanin colourant. Anthocyanin has been solvent-extracted from fruit pulps of Melastoma malabathricum. Different weight percentage of ferulic acid (FA) have been added to the anthocyanin solution and exposed to 17.55 lux UV-B irradiation for 93 days. The colour stability has been evaluated using Commission Internationale de l’Eclairage (CIE) colour system. The FA has been added to anthocyanin solution that contains.5 % trifluoroacetic acid (TFA) has been mixed with poly (vinyl alcohol) or PVA for the development of a coating system. The PVA–anthocyanin coating without FA has the most unstable colour. Coating with 3 % FA addition resulted in better colour stability. Colour stability has been analysed via lightness (L*), chromaticity(c*), hue angle (H°), coordinates a* and b* as well as colour saturation.